2016
DOI: 10.1590/s0100-204x2016000800006
|View full text |Cite
|
Sign up to set email alerts
|

Growth, mineral composition, fruit yield, and mycorrhizal colonization of feijoa in response to lime and phosphorus application

Abstract: -The objective of this work was to investigate the effect of liming and phosphorus fertilization on the growth, mineral composition of the leaves, fruit yield, and mycorrhizal colonization of young feijoa (Acca sellowiana) plants. Treatments consisted of four liming levels -0, 25, 50, and 100% of the dose required to raise the soil pH to 6.5 -and of five levels of P -0, 60, 120, 180, and 240 kg ha -1 P 2 O 5 -, placed in a randomized complete block design, in a split-plot arrangement, with three replicates. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…Although the soil P levels were considered to be very low (Table 1), the leaf nutrient contents (Figure 1) were in the normal or above normal range (CQFS-RS/ SC, 2016), as observed for all cultivars in 2015. This corroborates with the results already found for other temperate fruits such as apple and pear tree, which are rarely deficient in P (BRUNETTO et al, 2015;NAVA et al, 2017), which is mainly due to the longer period they are able to absorb the nutrient from the soil, as well as the association of the roots of these trees with mycorrhizal fungi hyphae, as verified by Nava et al (2016) for the feijoa tree. In 2014, the Santa Rita cultivar showed to be superior to the Amarelinha cultivar, but it did not present different P leaf contents in relation to the other evaluated cultivars.…”
Section: Block Ph Watersupporting
confidence: 91%
“…Although the soil P levels were considered to be very low (Table 1), the leaf nutrient contents (Figure 1) were in the normal or above normal range (CQFS-RS/ SC, 2016), as observed for all cultivars in 2015. This corroborates with the results already found for other temperate fruits such as apple and pear tree, which are rarely deficient in P (BRUNETTO et al, 2015;NAVA et al, 2017), which is mainly due to the longer period they are able to absorb the nutrient from the soil, as well as the association of the roots of these trees with mycorrhizal fungi hyphae, as verified by Nava et al (2016) for the feijoa tree. In 2014, the Santa Rita cultivar showed to be superior to the Amarelinha cultivar, but it did not present different P leaf contents in relation to the other evaluated cultivars.…”
Section: Block Ph Watersupporting
confidence: 91%
“…Soil Mg contents in the soil reached superior values at the critical level (above 1.0 cmol c kg -1 ), considered sufficient for adequate plant development (CQFS-RS/SC 2016). In addition to the increase in Ca and Mg availability to root uptake, lime application neutralizes acidity, endowing plants with a larger soil volume exploration capacity, and facilitating plant nutrient uptake (Nava et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In exchange for photosynthates, usable as an energy source for the formation, maintenance and functioning of mycorrhizal structures, the arbuscular mycorrhizal fungi hypha can provide up to 80 % of P, 25 % of nitrogen, 10 % of potassium, 25 % of zinc and 60 % of copper to the plant metabolism (Marschner and Dell, 1994;Gianinazzi et al, 2010). However, strawberry guava's yield potential may still not be expressed under natural soil pH conditions, similar to what has been observed in other fruit species which, in acid soils, present slower growth and low yield (Nava et al, 2016). To correct this, lime should be applied to increase the soil pH up to 6.0 for the majority of species (CQFS/RS-SC, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…Differences between presented study and Gucwa-Przepióra et al (2007) are associated with the use of phosphorus compounds which modify soil properties in terms of primary macronutrients availability (particularly P), what was not true for this study. Nava et al (2016) showed a positive influence of liming on mycorrhizal colonization effectiveness in Acca sellowiana. The discrepancy in the results may be due to the fact that, the effectiveness AMF colonization may depend on the mycorrhizal species and their tolerance to practices in crop management (Junior et al 2019), as well as on host plants and environmental conditions (Oehl et al 2003).…”
Section: Mycorrhizal Colonization Studiesmentioning
confidence: 92%
“…Interestingly, both of used amendments amplified significantly the development of arbuscules, and at the same time it led to a reduction of other mycorrhizal structures such as hyphae and vesicles. Previous studies presented various impacts of soil treatments such as liming (Gomes et al 2015;Heyburn et al 2017;Nava et al 2016) or application of lignite in combination with calcium phosphate (Gucwa-Przepióra et al 2007) on mycorrhizal colonization. The studies of Gucwa-Przepióra et al (2007), showed an increase in the development of AMF in Deschampsia cespitosa roots caused by the application of mixed calcium phosphate and lignite, but indicated that EC and pH did not affect native AM colonization level.…”
Section: Mycorrhizal Colonization Studiesmentioning
confidence: 99%